Comment on 'It's Not Factor Accumulation : Stylized Facts and Growth Models,' by William Easterly and Ross Levine - Romer, Paul (Washington, DC: World Bank, 2014)
When economists in the 1950s and 1960s used growth models to understand the experience of developing countries, they allowed for the possibility of technology differences between developing countries and the United States. But because they did not have a good theory for talking about the forces that determined the level of the technology-in the United States any more than in developing countries-technology factors tended to be pushed into the background in policy discussions. The new growth theory of the 1980s generated a counter reaction in the 1990s that Pete Klenow and Andres Rodriguez-Clare have called the 'neoclassical revival.' The article by William Easterly and Ross Levine is part of the next swing in the scholarly pendulum. It moves away from the critical assumption in the neoclassical revival that the level of technology is the same in all countries.